GAMBARAN POSTUR DAN KELUHAN MUSKULOSKELETAL PADA SISWA SMA NEGERI 10 BOGOR - Dini Nur Alpiah; Firdausiyah Rizki Amallia, Ema Trisnawati, Maria Emilia (CV. Adiba Aisha Amira, 2025)
Poor posture in teenagers can trigger musculoskeletal complaints which have an impact on long-term health. This study aims to describe body posture and musculoskeletal complaints in students at SMA Negeri 10 Bogor. The research method uses a descriptive approach with data collection through the Iowa Posture Test and Nordic Body Map questionnaires. The research sample was 293 students selected using accidental sampling technique. The results showed that 82.3% of students had poor posture, and musculoskeletal complaints were most commonly found in the hip area (mean score 2.08), followed by the neck and waist (1.93). Age and gender factors influence the risk of postural and musculoskeletal complaints. Therefore, education regarding ergonomic posture needs to be improved to prevent musculoskeletal disorders in adolescents.